Health and Safety in Health Care Settings: Review on Protection of Patients and Healthcare Workers - Althaale, Naif Jhaz; Alabbadi, Mohammed Aiydh Hamoud; Abdulwahab, Ahmed Rushdi Abdullatif; Alqahtani, Abdulraheem Ali; Almutairi, Turki Ayedh; Moamena, Ohoud Esam; Alalawi, Fatimah Mohammed; Alzahrani, Bandar Mousa; Alshalawi, Reema Abdullah; Alharbi, Eman Abdulmohsin; Alsarwan, Tahani Mansi; Alghamdi, Bashair Ali; et al. (Journal of Posthumanism, 2024)
Health and safety in healthcare settings constitute the foundation of quality medical services, ensuring that both patients and healthcare professionals operate in environments that minimize risks and prevent harm. The modern concept of safety culture emphasizes proactive risk identification rather than reactive incident management. Healthcare organizations increasingly recognize that maintaining a safe workplace directly influences patient care outcomes. Effective safety programs integrate organizational policies, behavioral training, and monitoring systems that promote accountability.